A cell-based potentiometric biosensor using the fungus Lentinus sajor-caju for permethrin determination in treated wood - Arip M.N.M.; Heng L.Y.; Ahmad M.; Ujang S. (Elsevier B.V., 2024)
Indexed by WOS/SCOPUS